Starosrpska poslovnopravna pismenost kao retorički fenomen - Pavlović, Slobodan (Slavistična revija, 2007)
The article examines the textual strucrture of Old-Serbian business-legal documents in the context of implicit and/or explicit rhetorical convetions that arose when the western-Catholic and eastern-Byzantine diplomatic norms collied.
Keywords: literacy; pismenost; pragmatika; retorika; rhetoric; sociolinguistics; sociolingvistika; srbščina